Leaf morphology and macronutrients in broadleaved trees in central Italy - Bussotti, Filippo; Borghini, Francesca; Celesti, Carlo; Leonzio, Claudio; Bruschi, Piero (Trees, 2000)
As part of an intensive monitoring programme (MON.I.TO, Intensive Monitoring of Forests in Tuscany), a 3-year survey was carried out, which included three tree species (beech, Fagus sylvatica L.; Turkey oak, Quercus cerris L.; holm-oak, Quercus ilex L.) located at six different sites. Leaves were sampled annually and analysed for nutrient concentrations (nitrogen, sulphur, phosphorus, magnesium, calcium, potassium and sodium) and morphological parameters (leaf area, dry weight, leaf mass per area, leaf thickness and leaf density). Results indicated considerable interannual variation of all the parameters. Differences between sampling sites indicated that, of all parameters measured, leaf mass per area could explain best the differences in field performance under conditions of stress. In fact, leaf mass per area was greater in the drier sites or when sea salt deposition occurred. Nevertheless, the variation of leaf mass per area over the 3 years did not reflect the differences in rainfall. Higher leaf mass per area was accompanied by lower concentrations of phosphorus and nitrogen, which could be a dilution effect due to an increase of structural carbon compounds in sclerophyllous leaves, as revealed by the total foliar content of these elements. Leaf mass per area as a measure of sclerophylly reached very high values among mesophile vegetation. Long-range transport of sea salt from coastal areas to mountain areas was mirrored in sodium concentrations of leaves.
Keywords: Fagus sylvatica; macronutrients; Quercus cerris; Quercus ilex; sclerophylly

Leaf morphology and macronutrients in broadleaved trees in central Italy - Bussotti, Filippo; Borghini, Francesca; Celesti, Carlo; Leonzio, Claudio; Bruschi, Piero (Trees, 2000)
As part of an intensive monitoring programme (MON.I.TO, Intensive Monitoring of Forests in Tuscany), a 3-year survey was carried out, which included three tree species (beech, Fagus sylvatica L.; Turkey oak, Quercus cerris L.; holm-oak, Quercus ilex L.) located at six different sites. Leaves were sampled annually and analysed for nutrient concentrations (nitrogen, sulphur, phosphorus, magnesium, calcium, potassium and sodium) and morphological parameters (leaf area, dry weight, leaf mass per area, leaf thickness and leaf density). Results indicated considerable interannual variation of all the parameters. Differences between sampling sites indicated that, of all parameters measured, leaf mass per area could explain best the differences in field performance under conditions of stress. In fact, leaf mass per area was greater in the drier sites or when sea salt deposition occurred. Nevertheless, the variation of leaf mass per area over the 3 years did not reflect the differences in rainfall. Higher leaf mass per area was accompanied by lower concentrations of phosphorus and nitrogen, which could be a dilution effect due to an increase of structural carbon compounds in sclerophyllous leaves, as revealed by the total foliar content of these elements. Leaf mass per area as a measure of sclerophylly reached very high values among mesophile vegetation. Long-range transport of sea salt from coastal areas to mountain areas was mirrored in sodium concentrations of leaves.
Keywords: Fagus sylvatica; macronutrients; Quercus cerris; Quercus ilex; sclerophylly